EFEKTIVITAS MODEL PEMBELAJARAN PBI (PROBLEM BASED INSTRUCTION) TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA MATA PELAJARAN BAHASA INDONESIA KELAS III SD - Turi Ashari (Universitas Negeri Medan, 2022)
Abstract : The Effectiveness of the PBI (Problem Based Instruction) Learning Model On Problem Solving Ability In Indonesia Language Subjects Grade III SD. This study aims to: 1) To find out the differences in the learning process of students to in a problem solving in the learning process of students to in a problem solving in the experimental class before and after the application of learning treatment using the PBI (Problem Based Instruction) learning model. 2) to find out weather there is effectiviness in a problem solving in the control class and the experimental class. Research subjects are students of SDN 88 Palembang. The number of targets/respondents is 60 people. Data collection technigues are carried out using: tests in the form of description. The discussion in this study shows that theeffectiveness of the PBI (Problem Based Instruction) learning mode on problem solving abilities.Keyword : PBI (Problem Based Instruction) Model, Problem Solving Ability Abstrak : Efektifitas Mode Pembelajaran PBI (Problem Based Instruction) Terhadap Kemampuan Pemecahan Masalah Pada Mata Pelajaran Bahasa Indonesia Kelas III SD. Penelitian ini bertujuan untuk : 1) Untuk mengetahui perbedaan proses pembelajaran siswa untuk dalam suatu pemecahan masalah pada kelas eksperimen sebelum dan sesudah diterapkannya perlakuan pembelajaran dengan menggunakan model pembelajaran PBI (Problem Based Instruction). 2) untuk mengetahui apakah terdapat keefektifan dalam suatu pemecahan masalah pada kelas kontrol dan kelas eksperimen. Subjek penelitian adalah siswa SDN 88 Palembang. Jumlah sasaran/responden sebanyak 60 orang. Teknik pengumpulan data dilakukan dengan menggunakan: Tes yang berupa uraian. Pembahasan dalam penelitian ini menunjukkan bahwa adanya keefektifan mode pembelajaran PBI (Problem Based Instruction) terhadap kemampuan pemecahan masalah.Kata Kunci : PBI (Problem Based Instruction) Kemampuan Pemecahan Masalah.